PENERAPAN PEMBELAJARAN BERBASIS PROYEK UNTUK MENUMBUHKAN PERILAKU KREATIF, MINAT BELAJAR, DAN KERJA SAMA SISWA KELAS V SD ATHALIA TANGERANG - Niko sudibjo; Novita Juwita Sari; Samuel Lukas (Akademika : Jurnal Teknologi Pendidikan, 2020)
Creativity and collaboration are softskills that are needed in the current era. Therefore, it is essential to habituate creativity and cooperation among students. However, the success of learning objectives is strongly influenced by students' interest in learning. Therefore, the objective ofthis classroom action research is to analyze the implementation of Project-Based Learning (PJBL) on learning interest, creative behaviour, and student collaboration of the 5th graders Athalia Elementary School Tangerang. The subject of this research was 9students in the Art, Culture, and Craft lesson. This classroom research focused on recycling products topic. The results showed that the implementation of PJBL in teaching Art, Culture, and Craft was able to increase the students learning interest, creative behaviour, and student collaboration. The result of thisof this study impliesthat if schools or teachers need to improve student’s creative behavior, students’ interest in learning, and student collaboration, then this project-based learning model is suitable to implement.